Health care of immigrant patients in Italy: the perspective of health professionals - Spinosa, Claudia; Angioletti, Laura; Balconi, Michela (Medicina e Morale, 2021)
Within a multicultural society, healthcare professionals (HPs) need to implement specific care pathways to meet the needs of patients with different cultural backgrounds who regularly present themselves in healthcare facilities in Italy. This study intends to examine the experiences and representations lived by HPs who deal with the care and management of foreign immigrant patients living in Italy, with chronic diseases. For this goal, a survey was conducted on a sample of 54 HPs recruited in hospital and outpatient facilities. The survey was analyzed with a quantitative analysis method. The results underlined that it is necessary to provide specific training paths to work with chronic immigrant patients, standardizing the training of medical staff both in hospitals and clinics, and providing for other types of professionals specialized in relations with foreign patients, to respond to all requests from foreign users, and not just healthcare ones. This study proposes a new survey model aimed at obtaining in-depth information on the representation of HPs towards the health and well-being of chronic immigrant patients, to provide concrete answers to the needs of the foreign population, providing for the collaboration of several specialised professionals.